Active Librarian Saving Users' Time - Luintel, Goma; Nyaichyai, Lila (Journal of Balkumari College, 2022)
A proactive librarian has a significant role to provide effective library service as well as saving users' time. This study aimed to explore the mechanism applied to save the time of the user, and to describe users' perspectives on time saving library services from Gyan Bikas Community library (GBCL). This research is based on primary data collected from the users, who had visited the library. The questionnaires and field observations tools were used. GBCL had provided different kinds of library services, particularly categorized as library service and community service. During both services, this study found that the time saving mechanisms of GCBL are proactive librarian, GBCL executive members along with field experts. The librarian was aware to internalize the value and importance of the Fourth Law of Library Science 'Save the time of the reader and practice them while offering the library services.